“E PLURIBUS UNUM” TESTING THE SPILLOVER CONCEPT IN AMERICA IN SEARCH OF A WORLD WORKING PEACE SYSTEM. - Useche, Ruben D. (Tufts Archival Research Center, 2017)
Submitted in partial fulfillment of the degree Masters of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: One of the key questions is to determine if Latin America is going into a deeper process of integration. Beyond failed experiences is Latin America engaged in a political integration process? This perspective emphasizes on an overarching process of integration than in single initiatives. Moreover, there is one theoretical trend that contents that integration should be seen as a process fueled by what they call “spillover”. This theory is Neo-functionalism. I argue that this framework of analysis is an appropriate tool to understand what is happening in Latin America and in the rest of the world, in terms of integration processes.My research question is whether or not South America is entering a process of political integration. A secondly related inquiry is whether the different initiatives of integration in the region could be seen as a process of “spillover” in The Americas. For this thesis, I have developed the following testable hypothesis: The greater the number of initiatives of integration in a region, the more opportunities to consolidate successful political integration. My study is centered on the process of integration in the Americas as being an overarching one. This research thesis is structured as follows: Introduction followed by a second section that shows a brief background. The third one is a review of literature of the theories of integration that from my humble point of view we should have to take a look (Federalism, Intergovernmentalism and Functionalism). However, I will follow in this thesis the functional approach and the natural law school, when analyzing integration in the Americas, particularly based on David Mitrany ideas and some others from Ernst Haas, but also comparing and extracting some ideas from other theories. The fourth part describes our understanding of the concepts of integration and spillover and its application to the regional and sub-regional cases of integration. The fifth section provides the conclusion.